(untitled) (Сучасні Проблеми Металургії, 2020)
The development of a physico-chemical model of methane behavior in the processes of solid-phase reduction of chromium-containing raw materials will allow us to create the technological basis for the production of multicomponent sponge ligatures. The reduction of oxides with methane is accompanied by the deposition of soot carbon. The negative effect of carbon black, which is blocking the reaction surface, can be eliminated by adding carbon dioxide or water vapor to methane. A thermodynamic analysis of the reduction of chromium oxide with mixtures of CH4-CO2, CH4-H2O was carried out. The effect of the partial replacement of methane by carbon on the thermodynamic preferences of the process is analyzed. A physicochemical model of the behavior of the CH4 molecule in the recovery process is proposed. The thermodynamic features of reduction at various ratios of СН4 are considered: (Н2О, СО2, О2), as well as the composition of the mixture (Н2О+СО2+О2), which ensure the conditions of solid-phase reduction of oxides and the product of carbide destruction. The use of CH4 + H2O + O2 mixtures in the reduction of chromium oxide is thermodynamically less effective. The use of a mixture of СН4 + Н2О + СО2 has a very insignificant effect on the conversion of methane, and also reduces the thermodynamic preference for the reduction of Cr2O3 in comparison with СН4 + Н2О + О2 and СН4 + Н2О. However, it should be noted that in addition to CO and H2, carbon can be present in the reduction products, so the high reduction potential in this process variant (C+CO+H2) can be used to reduce oxides. The reduction of chromium oxide with mixtures of СН4 + Н2О + О2, СН4 + Н2О, and СН4 + Н2О + СО2 can be thermodynamically realized in the temperature range excluding the melting of the charge. As a result of this process, a carbide phase is formed, as well as a gas phase, which has a high reduction potential and can be used in further technological schemes. Meanwhile, it seems possible to control the carbon content in the sponge ligature by selecting the optimal composition of the source gas mixture.